Cas9-specific immune responses compromise local and systemic AAV CRISPR therapy in multiple dystrophic canine models - Hakim, Chady H.; Kumar, Sandeep R. P.; Pérez-López, Dennis O.; Wasala, Nalinda B.; Zhang, Dong; Yue, Yongping; Teixeira, James; Pan, Xiufang; Zhang, Keqing; Million, Emily D.; Nelson, Christopher E.; Metzger, Samantha; et al. (Nature communications, 2021)
Adeno-associated virus (AAV)-mediated CRISPR-Cas9 editing holds promise to treat many diseases. The immune response to bacterial-derived Cas9 has been speculated as a hurdle for AAV-CRISPR therapy. However, immunological consequences of AAV-mediated Cas9 expression have thus far not been thoroughly investigated in large mammals. We evaluate Cas9-specific immune responses in canine models of Duchenne muscular dystrophy (DMD) following intramuscular and intravenous AAV-CRISPR therapy. Treatment results initially in robust dystrophin restoration in affected dogs but also induces muscle inflammation, and Cas9-specific humoral and cytotoxic T-lymphocyte (CTL) responses that are not prevented by the muscle-specific promoter and transient prednisolone immune suppression. In normal dogs, AAV-mediated Cas9 expression induces similar, though milder, immune responses. In contrast, other therapeutic (micro-dystrophin and SERCA2a) and reporter (alkaline phosphatase, AP) vectors result in persistent expression without inducing muscle inflammation. Our results suggest Cas9 immunity may represent a critical barrier for AAV-CRISPR therapy in large mammals. The Cas9-specific T cell response has been speculated to impair CRISPR therapy. Here, the authors show that local and systemic AAV CRISPR therapy induces cytotoxic killing and eliminates rescued dystrophin in canine models of Duchenne muscular dystrophy.